Unlimited Paid Time Off Policies: Unlocking the Best and Unleashing the Beast - de Bloom, Jessica; Syrek, Christine J.; Kühnel, Jana; Vahle-Hinz, Tim (Frontiers in Psychology, 2022)
Unlimited paid time off policies are currently fashionable and widely discussed by HR professionals around the globe. While on the one hand, paid time off is considered a key benefit by employees and unlimited paid time off policies (UPTO) are seen as a major perk which may help in recruiting and retaining talented employees, on the other hand, early adopters reported that employees took less time off than previously, presumably leading to higher burnout rates. In this conceptual review, we discuss the theoretical and empirical evidence regarding the potential effects of UPTO on leave utilization, well-being and performance outcomes. We start out by defining UPTO and placing it in a historical and international perspective. Next, we discuss the key role of leave utilization in translating UPTO into concrete actions. The core of our article constitutes the description of the effects of UPTO and the two pathways through which these effects are assumed to unfold: autonomy need satisfaction and detrimental social processes. We moreover discuss the boundary conditions which facilitate or inhibit the successful utilization of UPTO on individual, team, and organizational level. In reviewing the literature from different fields and integrating existing theories, we arrive at a conceptual model and five propositions, which can guide future research on UPTO. We conclude with a discussion of the theoretical and societal implications of UPTO.